2014
DOI: 10.1364/ol.39.005196
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffraction-limited radius measurements of microcylinders using conventional bright-field optical microscopy

Abstract: A technique for measuring the radius of dielectric microcylinders with subdiffraction-limited precision is presented. Diffraction fringes arising from the dielectric cylinder are measured using conventional bright-field optical microscopy and compared with theory to deduce the radii. The technique has been demonstrated measuring the radii of the major-ampullate silks from Plebs eburnus spiders. Precision better than 50 nm is demonstrated, using a standard optical microscope with a numerical aperture of 0.6 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For example, in 2004 Warken and Giessen demonstrated that the profile of subwavelength-diameter MNFs could be measured by the diffraction pattern, with a resolution of ±50 nm over a length of 5 cm [155] . Similarly, a series of optical microscopy techniques have also been reported for measuring the MNF diameter with a resolution of below 50 nm [156159] . In 2006, Sumetsky et al .…”
Section: Fabrication Of Optical Mnfsmentioning
confidence: 99%
“…For example, in 2004 Warken and Giessen demonstrated that the profile of subwavelength-diameter MNFs could be measured by the diffraction pattern, with a resolution of ±50 nm over a length of 5 cm [155] . Similarly, a series of optical microscopy techniques have also been reported for measuring the MNF diameter with a resolution of below 50 nm [156159] . In 2006, Sumetsky et al .…”
Section: Fabrication Of Optical Mnfsmentioning
confidence: 99%
“…Silk size was measured optically by measuring the separation of the diffraction fringes observed under parallelpolarized illumination with a wavelength of 546 nm and comparing them to theory [13]. Here, the silk size is quantified as the radii of the silk cylinders, which are assumed to be identical.…”
Section: Measuring Silk Radiimentioning
confidence: 99%